Proceedings of the 16th Annual ACM Symposium on User Interface Software and Technology 2003
DOI: 10.1145/964696.964720
|View full text |Cite
|
Sign up to set email alerts
|

Stylus input and editing without prior selection of mode

Abstract: This paper offers a solution to the mode problem in computer sketch/notetaking programs. Conventionally, the user must specify the intended "draw" or "command" mode prior to performing a stroke. This necessity has proven to be a barrier to the usability of pen/stylus systems. We offer a novel Inferred-Mode interaction protocol that avoids the mode hassles of conventional sketch systems. The system infers the user's intent, if possible, from the properties of the pen trajectory and the context of the trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 13 publications
(8 reference statements)
0
30
0
Order By: Relevance
“…Thus we decided to remove the first trial of each set of 5 repeated trials from our analysis. Our analysis revealed a significant effect for Delimiter Technique, F (3,21) =18, p<.001. Post-hoc (Bonferroni) pairwise comparisons revealed that Timeout was significantly slower than all other delimiters (p<.01), but completion times for Pigtail, Handle, and Button did not differ significantly from one another.…”
Section: Completion Time: Main Experimental Blockmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus we decided to remove the first trial of each set of 5 repeated trials from our analysis. Our analysis revealed a significant effect for Delimiter Technique, F (3,21) =18, p<.001. Post-hoc (Bonferroni) pairwise comparisons revealed that Timeout was significantly slower than all other delimiters (p<.01), but completion times for Pigtail, Handle, and Button did not differ significantly from one another.…”
Section: Completion Time: Main Experimental Blockmentioning
confidence: 66%
“…A tap is used as a cue to the system to attempt to recognize the preceding ink stroke(s). Stylus input without prior selection of mode [21] takes a recognition-based approach to classify lassos drawn during ink mode as selection gestures, and to provide options in a menu if it is uncertain.…”
Section: Related Workmentioning
confidence: 99%
“…pressing a dedicated key(s) to get into gesture mode and pressing it again to get out of the gesture mode, required explicit effort on part of the user, were not intuitive and posed usability issues. Previous studies done around switching techniques in pen/stylus based interfaces have also proven that actions where the user must conventionally specify an intended mode before performing a task, end up being barriers to the usability of such systems [7,8,9]. In order to avoid explicit mode switching, we have come up with two different interactions, where in gesture indication and mode switching happen simultaneously.…”
Section: Gesture Invocationmentioning
confidence: 99%
“…However, WeMet system didn't go further beyond simple sketch support on PC-based meeting environment. One step beyond sketching without recognition, Saund et al and Rubine et al [9,10] proposed various PC-based approaches with handwritten text and gesture recognition. Devices bearing an active writable display (like Tablet PC's and PDA's) can be expensive to deploy.…”
Section: Related Workmentioning
confidence: 99%